Designing an immersive interactive environment for IIoT-enhanced vertical centrifugal casting - Anadkat, Dhaval; Sata, Amit; Shukla, Minal; Jarboui, Slaheddine; Mobarsa, Divya (Frontiers in Education, 2025)
Metal casting is among humanity’s most ancient manufacturing methods in which, molten metal is poured into a mold of a desired shape. Despite its long history, this field has not fully embraced cutting-edge technologies like IIoT, AR/VR, and the metaverse. Emerging technologies like AR/VR and Metaverse have become popular and offer exciting possibilities for metal casting applications. A physical set up of metal casting integrated with IIoT is designed and developed in immersive interactive environment to utilise the most recent technology in manufacturing. The goal is to reinforce research, stimulate innovation, and develop technical expertise, for which a conceptual framework is designed to create Immersive Interactive Environment for metal casting, specifically for Vertical Centrifugal Casting (VCC). In this process, metal is poured in to the rotating mold to produce cylindrical components. The present work focuses on development of young and emerging talent to build their skills in traditional processes like casting through experimental learning and develop the learning environment for the young and curios minds. Ultimate aim is to nurture innovation and to bridge the gap that exists between traditional manufacturing methodologies and contemporary technological enhancements.